Posted by **Mark** on Thursday, March 14, 2013 at 12:49pm.

y= (cos^3 x) (cos 3x)

I got -3 sin(3x) cos^3x - 3 sin(x) cos (3x) cos^2 (x) using the product rule

Is this right? Thanks.

- Cos-Derivative -
**Damon**, Thursday, March 14, 2013 at 1:16pm
yes

- Cos-Derivative -
**Mark**, Thursday, March 14, 2013 at 1:27pm
Thanks!

## Answer This Question

## Related Questions

- tigonometry - expres the following as sums and differences of sines or cosines ...
- TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...
- Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...
- algebra - Can someone please help me do this problem? That would be great! ...
- Calculus 12th grade (double check my work please) - 1.)Find dy/dx when y= Ln (...
- trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...
- calculus - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x...
- Calc. - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln...
- pre-cal - Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos ...
- Precal - I do not understand how to do this problem ((sin^3 A + cos^3 A)/(sin A...

More Related Questions